Positive electrode material and preparation method thereof, positive plate, battery and electric device

By forming a cladding layer containing carboxyl functional groups on the surface of lithium manganate, the problem of manganese ion dissolution caused by the reaction of lithium manganate with electrolyte is solved, and the circulation performance and energy density of the battery are improved.

CN119852334APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311352394.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Lithium manganate easily reacts with electrolyte in lithium-ion batteries, resulting in the dissolution of manganese ions, affecting the activity of active materials, and reducing the capacity and circulation performance of the battery.

Method used

By forming a clad layer containing carboxyl functional groups on the surface of lithium manganate, the reaction of carboxyl functional groups with residual alkali on the surface of lithium manganate is used to generate ester functional groups to form an ion-conducting polymer, realizing in-situ clad of lithium manganate and enhancing the binding firmness of the clad layer and lithium manganate.

Benefits of technology

The contact between lithium manganese oxide and the electrolyte is reduced, the dissolution of manganese ions is inhibited, the reaction between the electrode active material and the electrolyte is reduced, and the circulation performance and energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852334A_ABST
    Figure CN119852334A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a positive plate, a battery and a power utilization device, the positive electrode material comprises an inner core and a coating layer at least partially coating the surface of the inner core, the inner core at least comprises lithium manganate, the coating layer comprises a reaction product of a compound containing a carboxyl functional group and residual alkali on the surface of the lithium manganate, and the surface of the lithium manganate is coated with the coating layer. The reaction product contains an ester functional group. A compound containing a carboxyl functional group of a coating layer reacts with core lithium manganate to generate a compound containing an ester functional group and form a conductive ion polymer, so that the surface of the core lithium manganate is coated with the compound containing the carboxyl functional group of the coating layer in situ, and in-situ coating of an electrode active material is realized; the bonding firmness of the coating layer and the lithium manganate is improved through the covalent bond, so that the lithium manganate is coated in the inner core, the contact between the lithium manganate and an electrolyte is reduced, the dissolution of manganese ions is inhibited, the reaction between an electrode active material and the electrolyte is reduced, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to positive electrode materials and preparation methods thereof, positive electrode sheets, batteries and electrical devices. Background Art

[0002] Lithium manganese oxide is one of the main active materials of lithium-ion batteries. Lithium manganese oxide batteries have good energy density and cycle retention performance. However, during use, lithium manganese oxide easily reacts with the electrolyte, resulting in the dissolution of manganese ions, affecting the activity of the active material, thereby reducing the capacity and cycle performance of the battery. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode material that reduces the contact between the active material and the electrolyte and improves the cycle performance of the battery.

[0004] In order to achieve the above-mentioned objectives, the embodiments of the present application provide a positive electrode material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device.

[0005] In a first aspect, an embodiment of the present application proposes a positive electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the core comprises at least lithium manganese oxide, and the coating layer comprises a reaction product of a compound containing a carboxyl functional group and residual alkali on the surface of the lithium manganese oxide, and the reaction product contains an ester functional group.

[0006] Therefore, in the technical solution of the embodiment of the present application, the positive electrode material is arranged into a core-shell structure, and the compound containing carboxyl functional groups in the coating layer reacts with the inner core lithium manganese oxide to generate a compound containing ester functional groups, thereby forming an ion-conducting polymer, so that the compound containing carboxyl functional groups in the coating layer is in situ coated on the surface of the inner core lithium manganese oxide, thereby realizing in situ coating of the electrode active material, and improving the firmness of the bonding between the coating layer and lithium manganese oxide through covalent bonds, thereby coating the lithium manganese oxide in the inner core, reducing the contact between lithium manganese oxide and the electrolyte, and inhibiting the dissolution of manganese ions, thereby reducing the reaction of the electrode active material with the electrolyte, and improving the cycle performance of the battery.

[0007] It should be noted that in the embodiments of the present application, since lithium manganese oxide is exposed to moisture and CO2 in the air during the preparation or storage process, there will be residual alkali residues on the surface of the lithium manganese oxide, such as lithium hydroxide, lithium carbonate and lithium bicarbonate. The compound containing a carboxyl functional group reacts with these residual alkalis to generate carboxyl groups, thereby fixing the material of the coating layer on the outer surface of the lithium manganese oxide to form an in-situ coating structure.

[0008] In any embodiment, in the structural formula of a single compound containing a carboxyl functional group, the number of carboxyl groups is 1 to 5. Sufficient carboxyl groups can increase the consumption rate of residual alkali, reduce the residual alkali, and at the same time improve the firmness of the connection between the coating layer and the core. When the number of carboxyl groups is 1 to 5, it can not only increase the binding rate of residual alkali and carboxyl groups, but also reduce the situation where the unreacted carboxyl groups increase the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and improve the energy density of the battery; optionally, the number of carboxyl groups is 1 to 4, which can further reduce the residual alkali, reduce the dissolution of manganese ions, and improve the energy density of the battery.

[0009] In any embodiment, the compound containing a carboxyl functional group includes at least one of 3-ethoxypropionic acid, fumaric acid, butanetetracarboxylic acid and biphenyl-3,3',5,5'-pentacarboxylic acid.

[0010] In any embodiment, the compound containing carboxyl functional group further includes a group containing nitrogen atoms. When the compound containing carboxyl functional group further includes a nitrogen-containing group, the coordination effect between manganese and nitrogen can be used to further reduce the dissolution of manganese ions and improve the cycle performance of the battery.

[0011] In any embodiment, in the structural formula of a single compound containing a carboxyl functional group, the number of the nitrogen atom-containing groups is 1 to 4, which can reduce the mass proportion of the coating layer, reduce the content of inactive substances, and increase the content of active substances, thereby increasing the energy density of the battery; optionally, the number of the nitrogen atom-containing groups is 1 to 2.

[0012] In any embodiment, the nitrogen-containing group includes at least one of -NH2, -N- and -N=N-. Using at least one of the above nitrogen-containing groups is more conducive to the coordination and complexation of nitrogen atoms and manganese ions, improving the firmness of the coating layer and the core, and thus improving the energy density and cycle performance. Preferably, using -N=N-, the double bond electronegativity is stronger, which is more conducive to the coordination and complexation with the metal manganese ion.

[0013] In any embodiment, the compound containing a carboxyl functional group includes at least one of ethylenediaminetetraacetic acid, nitrilotriacetic acid, 4-methyl-1-piperazineacetic acid and N,N-dihydroxyethylglycine. Using at least one of the above nitrogen-containing groups can further improve the coordination and complexing effect of nitrogen atoms and manganese atoms, improve the firmness of the combination of the coating layer and the core, and thus improve the energy density and cycle performance.

[0014] In any embodiment, the pH value of the kernel in a mixture of a kernel and water at a mass ratio of 1:10 is 7 to 11. Due to the presence of a water washing step in the battery preparation process, there will be residual alkali residues on the surface of the kernel material. These residual alkalis can react with carboxyl-containing compounds to form ester groups, thereby fixing the carboxyl-containing compounds on the surface of the kernel. When the content of residual alkali is measured by the kernel pH value, the pH value of the kernel in a mixture of a kernel and water at a mass ratio of 1:10 is 7 to 11, which can increase the binding rate of the carboxyl-containing compound and the residual alkali, improve the coating effect, and thus improve the battery cycle performance. Optionally, the pH value is 8 to 10, which can further increase the binding rate of the carboxyl-containing compound and the residual alkali, improve the coating effect, and thus improve the battery cycle performance.

[0015] In any embodiment, the mass fraction of the material of the coating layer is w1, and the mass fraction of the material of the core is w2, wherein 0.05%≤w1:(w1+w2)≤1%, when the mass fraction of the coating layer in the positive electrode material is 0.05% to 1%, the thickness of the coating layer can be made appropriate, which is conducive to the rapid transmission of ions and electrons of the positive electrode material, reduces the impact on the energy density of the battery, and maintains a good coating effect, reducing the contact between the active material and the electrolyte; optionally, 0.1%≤w1:(w1+w2)≤0.5%. Within this range, the impact on the energy density of the battery can be further reduced, while maintaining a good coating effect and reducing the contact between the active material and the electrolyte.

[0016] In any embodiment, the thickness of the coating layer is 1 to 20 nm, which can improve the coating performance of the core while reducing the direct contact between the core active material and the electrolyte, reduce the impact on the rapid transmission of lithium ions, and reduce the impact on the energy density of the battery; optionally, the thickness of the coating layer is 1 to 10 nm, which can further improve the coating performance of the core while reducing the direct contact between the core active material and the electrolyte.

[0017] In any embodiment, the lithium manganate includes doped lithium manganate, and the molecular formula of the doped lithium manganate includes LiMn 2-α X α O4;

[0018] Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium.

[0019] The value of α is 0.001~0.5.

[0020] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0021] A coating layer is formed outside the core material lithium manganate, and the carboxyl group in the coating layer material reacts with the residual alkali on the surface of the core material lithium manganate to obtain a positive electrode material.

[0022] By forming a coating layer outside the core material lithium manganate, and allowing the carboxyl group in the coating layer material to react with the core material lithium manganate, the positive electrode material can improve the firmness of the connection between the coating layer and the core and reduce the dissolution of manganese ions in the core material.

[0023] In any embodiment, the step of forming a coating layer outside the core material lithium manganese oxide, and allowing the carboxyl group in the coating layer material to react with the core material lithium manganese oxide to obtain the positive electrode material comprises:

[0024] The lithium manganate is reacted with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material.

[0025] By reacting lithium manganate with a compound containing both a carboxyl functional group and a nitrogen-containing group, a coating layer is formed on the surface of the lithium manganate. The positive electrode material can further reduce the dissolution of manganese ions by forming a coordination bond between the nitrogen-containing group and the manganese ion while the carboxyl functional group reacts with the residual alkali in the lithium manganate.

[0026] In any embodiment, the step of reacting lithium manganate with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material comprises:

[0027] The lithium manganate is mixed with a solution of ethylenediaminetetraacetic acid, so that the carboxyl group in the ethylenediaminetetraacetic acid reacts with the residual alkali on the surface of the lithium manganate to form a coating layer on the surface of the lithium manganate, thereby obtaining a positive electrode material.

[0028] By mixing lithium manganate with a solution of ethylenediaminetetraacetic acid, the carboxyl group in the ethylenediaminetetraacetic acid reacts with the lithium manganate to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material. The double bond electronegativity of the nitrogen-containing group is stronger, which is more conducive to coordination and complexing with metal manganese ions, thereby reducing the dissolution of manganese ions.

[0029] In any embodiment, the reaction time is 0.5 to 5 hours. The reaction time affects the effect of the connection between the coating layer and the core. Within the range of 0.5 to 5 hours, the coating layer and the core can fully react to improve the coating effect and reduce the impact on production efficiency. Optionally, the reaction time is 1 to 2 hours, which further allows the coating layer and the core to fully react and reduce the impact on production efficiency; and / or,

[0030] The reaction temperature is 5-50°C, which can not only make the reaction speed of the coating layer and the core suitable and reduce the impact on production efficiency, but also reduce the probability of side reactions and reduce the impact on the formation of the coating layer; optionally, the polymerization reaction time is 20-40°C, which can further make the reaction speed of the coating layer and the core suitable, reduce the impact on production efficiency, reduce the probability of side reactions and reduce the impact on the formation of the coating layer.

[0031] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the positive electrode material of the second aspect of the present application.

[0032] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet of the third aspect of the present application.

[0033] In a fifth aspect, an embodiment of the present application proposes an electrical device, comprising the battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0035] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0036] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0037] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0038] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0039] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0040] Description of reference numerals:

[0041] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0042] The following specifically discloses the embodiments of the positive electrode material and preparation method thereof, positive electrode sheet, battery and electric device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0047] Lithium manganese oxide is one of the main active materials of lithium-ion batteries. Lithium manganese oxide batteries have good energy density and cycle retention performance. However, during use, lithium manganese oxide easily reacts with the electrolyte, resulting in the dissolution of manganese ions, affecting the activity of the active material, thereby reducing the capacity and cycle performance of the battery.

[0048] Therefore, there are endless technologies for improving the direct contact between lithium manganate and electrolyte. For example, a positive electrode of a lithium manganate material battery has a higher specific capacity and good cycle performance by adopting a lithium manganate positive electrode material coated with tin oxide, and has better high temperature cycle performance. Among them, the tin oxide coating layer is more dense, and the tin oxide layer can still maintain a good fit with the main lithium manganate material during the long-term cycle process, and it is not easy to separate. Therefore, the tin oxide of the outer layer can maintain the protection of the internal lithium manganate for a long time, prevent the corrosion of the lithium manganate by the external HF, and then effectively improve the cycle stability of the material. However, since the coating layer is usually coated on the surface of the kernel by a high-temperature calcination treatment method during the coating process, the production cost is greatly increased. The coating layer and the lithium manganate rely solely on physical action, and its structural stability needs to be further improved.

[0049] Unexpectedly, by forming a coating layer containing an ester functional group on the surface of the lithium manganate core, the direct contact between the electrode active material and the electrolyte can be reduced. At the same time, the compound containing a carboxyl functional group can spontaneously react with the residual alkali on the surface of the lithium manganate to form an ester group, so that the coating layer is spontaneously coated on the surface of the lithium manganate core, which improves the firmness of the binding and reduces the dissolution of manganese ions, greatly reducing the production cost. In addition, the compound containing a carboxyl functional group is covalently bonded to the residual alkali on the surface of the lithium manganate core, so that the compound containing a carboxyl functional group is more firmly bound to the surface of the lithium manganate core, thereby improving the structural stability of the coating layer and the core active material, thereby improving the cycle performance of the battery.

[0050] In a first aspect, an embodiment of the present application proposes a positive electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the core comprises at least lithium manganese oxide, and the coating layer comprises a reaction product of a compound containing a carboxyl functional group and residual alkali on the surface of the lithium manganese oxide, and the reaction product contains an ester functional group.

[0051] Therefore, in the technical solution of the embodiment of the present application, the positive electrode material is arranged into a core-shell structure, and the compound containing carboxyl functional groups in the coating layer reacts with the inner core lithium manganese oxide to generate a compound containing ester functional groups, thereby forming an ion-conducting polymer, so that the compound containing carboxyl functional groups in the coating layer is in situ coated on the surface of the inner core lithium manganese oxide, thereby realizing in situ coating of the electrode active material, and improving the firmness of the bonding between the coating layer and lithium manganese oxide through covalent bonds, thereby coating the lithium manganese oxide in the inner core, reducing the contact between lithium manganese oxide and the electrolyte, and inhibiting the dissolution of manganese ions, thereby reducing the reaction of the electrode active material with the electrolyte, and improving the cycle performance of the battery.

[0052] It should be noted that in the embodiments of the present application, since lithium manganese oxide is exposed to moisture and CO2 in the air during the preparation or storage process, there will be residual alkali residues on the surface of the lithium manganese oxide, such as lithium hydroxide, lithium carbonate and lithium bicarbonate. The compound containing a carboxyl functional group reacts with these residual alkalis to generate carboxyl groups, thereby fixing the material of the coating layer on the outer surface of the lithium manganese oxide to form an in-situ coating structure.

[0053] In any embodiment, in the structural formula of a single compound containing a carboxyl functional group, the number of carboxyl groups is 1 to 5. Sufficient carboxyl groups can increase the consumption rate of residual alkali, reduce the residual alkali, and improve the firmness of the connection between the coating layer and the core. When the number of carboxyl groups is 1 to 5, it can not only provide an increase in the binding rate of residual alkali and carboxyl groups, but also reduce the situation where the unreacted carboxyl groups increase the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and improve the energy density of the battery. The number of carboxyl groups can be 1, 2, 3, 4, 5 or 6; optionally, the number of carboxyl groups is 1 to 4, which can further reduce the residual alkali, reduce the dissolution of manganese ions, and improve the energy density of the battery.

[0054] In any embodiment, the compound containing a carboxyl functional group includes at least one of 3-ethoxypropionic acid, fumaric acid, butanetetracarboxylic acid and biphenyl-3,3',5,5'-pentacarboxylic acid.

[0055] In any embodiment, the compound containing carboxyl functional group also includes a compound containing a group of nitrogen atoms. When the compound containing carboxyl functional group also includes a nitrogen-containing group, the coordination effect between manganese and nitrogen can be used to further reduce the dissolution of manganese ions and improve the cycle performance of the battery.

[0056] In any embodiment, in the structural formula of a single compound containing a carboxyl functional group, the number of nitrogen atom-containing groups is 1 to 4, which can reduce the mass proportion of the coating layer, reduce the content of inactive substances, and increase the content of active substances, thereby increasing the energy density of the battery. The number of nitrogen atom-containing groups can be 1, 2, 3 or 4; optionally, the number of nitrogen atom-containing groups is 1 to 2.

[0057] In any embodiment, the nitrogen atom-containing group includes at least one of -NH2, -N- and -N=N-. The use of at least one of the above nitrogen atom-containing groups is more conducive to the coordination and complexation of nitrogen atoms and manganese ions, improves the firmness of the combination of the coating layer and the core, and thus improves the energy density and cycle performance. Preferably, -N=N- is used, the double bond electronegativity is stronger, and it is more conducive to the coordination and complexation with metal manganese ions. In some embodiments of the present application, the nitrogen atom-containing group may only include any one of -NH2, -N- and -N=N-. In some embodiments of the present application, the nitrogen atom-containing group may simultaneously include two or three of -NH2, -N- and -N=N-.

[0058] In any embodiment, the compound containing the carboxyl functional group includes at least one of ethylenediaminetetraacetic acid, nitrilotriacetic acid, 4-methyl-1-piperazineacetic acid and N, N-dihydroxyethylglycine. The use of at least one of the above-mentioned nitrogen-containing groups can further improve the coordination and complexing effect of nitrogen atoms and manganese atoms, improve the firmness of the coating layer and the core, and thus improve the energy density and cycle performance. In some embodiments of the present application, the compound containing the nitrogen atom group at the same time may only include any one of ethylenediaminetetraacetic acid, nitrilotriacetic acid, 4-methyl-1-piperazineacetic acid and N, N-dihydroxyethylglycine. In some embodiments of the present application, the compound containing the nitrogen atom group at the same time may only include any two or more of ethylenediaminetetraacetic acid, nitrilotriacetic acid, 4-methyl-1-piperazineacetic acid and N, N-dihydroxyethylglycine.

[0059] In any embodiment, the pH value of the core in the mixed solution with a mass ratio of core to water of 1:10 is 7-11. Due to the presence of a water washing step in the battery preparation process, there will be residual alkali residues on the surface of the core material. These residual alkalis can react with carboxyl-containing compounds to form ester groups, thereby fixing the carboxyl-containing compounds on the surface of the core. When the content of residual alkali is measured by the core pH value, the core in the mixed solution with a mass ratio of core to water of 1:10 has a pH value of 7-11, which can increase the binding rate of carboxyl-containing compounds and residual alkali, improve the coating effect, and thus improve the battery cycle performance. Optionally, the pH value is 8-10, which can further increase the binding rate of carboxyl-containing compounds and residual alkali, improve the coating effect, and thus improve the battery cycle performance. It should be noted that the above pH value can be determined by the following method: 1 part of the core material, such as lithium manganate, is mixed with 10 parts of pure water, stirred for 15 minutes, and the pH value of the mixed solution is determined using a pH meter.

[0060] In any embodiment, the mass fraction of the material of the coating layer is w1, and the mass fraction of the material of the core is w2, wherein 0.05%≤w1:(w1+w2)≤1%. When 0.05% to 1%, the coating layer thickness can be made appropriate, which is conducive to the rapid transmission of ions and electrons of the positive electrode material, reduces the impact on the energy density of the battery, and maintains a good coating effect, reducing the contact between the active material and the electrolyte; the value of w1:(w1+w2) can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%. Optionally, 0.1%≤w1:(w1+w2)≤0.5%. Within this range, the impact on the energy density of the battery can be further reduced, while maintaining a good coating effect and reducing the contact between the active material and the electrolyte.

[0061] In any embodiment, the thickness of the coating layer is 1 to 20 nm, which can improve the coating performance of the core while reducing the direct contact between the core active material and the electrolyte, reduce the impact on the rapid transmission of lithium ions, and reduce the impact on the energy density of the battery; the thickness of the coating layer can be 1 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, or 20 nm. Optionally, the thickness of the coating layer is 1 to 10 nm, which can further improve the coating performance of the core while reducing the direct contact between the core active material and the electrolyte.

[0062] In any embodiment, the lithium manganate includes doped lithium manganate, and the molecular formula of the doped lithium manganate includes LiMn 2-α X α O4;

[0063] Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium.

[0064] The value of α is 0.001~0.5.

[0065] It should be noted that in the embodiments of the present application, the chemical formula of lithium manganese oxide is the chemical formula of the material used in the preparation process. In the positive electrode sheet, battery cell, and electrical equipment, due to the formation and circulation processes, those skilled in the art can understand that the elements in the chemical formula of lithium manganese oxide may be lost. For example, the O element will be consumed, so there will be a decrease in the O element in the measured lithium manganese oxide.

[0066] It should be noted that in the positive electrode sheets, battery cells, and electrical equipment, lithium ions will be consumed during the formation and circulation processes, so the measured lithium content in the positive electrode active material will decrease. At the same time, if the positive and negative electrode sheets are supplemented with lithium, after the formation and circulation processes, the measured lithium content in the positive electrode active material will increase.

[0067] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0068] A coating layer is formed outside the core material lithium manganate, and the carboxyl group in the coating layer material reacts with the residual alkali on the surface of the core material lithium manganate to obtain a positive electrode material.

[0069] By forming a coating layer outside the core material lithium manganate, and allowing the carboxyl group in the coating layer material to react with the core material lithium manganate, the positive electrode material can improve the firmness of the connection between the coating layer and the core and reduce the dissolution of manganese ions in the core material.

[0070] In any embodiment, the step of forming a coating layer outside the core material lithium manganese oxide, and allowing the carboxyl group in the coating layer material to react with the core material lithium manganese oxide to obtain the positive electrode material comprises:

[0071] The lithium manganate is reacted with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material.

[0072] By reacting lithium manganate with a compound containing both a carboxyl functional group and a nitrogen-containing group, a coating layer is formed on the surface of the lithium manganate. The positive electrode material can further reduce the dissolution of manganese ions by forming a coordination bond between the nitrogen-containing group and the manganese ion while the carboxyl functional group reacts with the residual alkali in the lithium manganate.

[0073] In any embodiment, the step of reacting lithium manganate with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material comprises:

[0074] The lithium manganate is mixed with a solution of ethylenediaminetetraacetic acid, so that the carboxyl group in the ethylenediaminetetraacetic acid reacts with the residual alkali on the surface of the lithium manganate to form a coating layer on the surface of the lithium manganate, thereby obtaining a positive electrode material.

[0075] By mixing lithium manganate with a solution of ethylenediaminetetraacetic acid, the carboxyl group in the ethylenediaminetetraacetic acid reacts with the lithium manganate to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material. The double bond electronegativity of the nitrogen-containing group is stronger, which is more conducive to coordination and complexing with metal manganese ions, thereby reducing the dissolution of manganese ions.

[0076] In any embodiment, the reaction time is 0.5 to 5 hours, and the reaction time affects the effect of the connection between the coating layer and the core. Within the range of 0.5 to 5 hours, the coating layer and the core can fully react to improve the coating effect and reduce the impact on production efficiency. The reaction time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours; optionally, the reaction time is 1 to 2 hours, which further allows the coating layer to fully react with the core and reduces the impact on production efficiency; and / or,

[0077] The reaction temperature is 5-50°C, which can not only make the reaction speed of the coating layer and the core suitable and reduce the impact on production efficiency, but also reduce the probability of side reactions and reduce the impact on the formation of the coating layer. The reaction temperature can be 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C; optionally, the polymerization reaction time is 20-40°C, which can further make the reaction speed of the coating layer and the core suitable, reduce the impact on production efficiency, reduce the probability of side reactions and reduce the impact on the formation of the coating layer.

[0078] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the positive electrode material of the second aspect of the present application.

[0079] In some embodiments of the present application, the positive electrode sheet includes a positive electrode slurry, and the positive electrode slurry includes a positive electrode material, a conductive agent, and a binder, wherein the mass ratio of the positive electrode material, the conductive agent, and the binder can be (0.5-20): (0.5-10): (70-99), and the mass ratio between the conductive agent, the binder, and the positive electrode material can be appropriately used to improve the cycle performance of the battery while ensuring the battery energy density. Optionally, the mass ratio between the conductive agent, the binder, and the positive electrode material is (1-2): (1.5-2.5): (94.5-96.5).

[0080] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the positive electrode material of the second aspect of the present application.

[0081] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0082] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0083] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0084] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0085] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0086] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet of the third aspect of the present application.

[0087] In any embodiment, the battery comprises a primary battery or a secondary battery.

[0088] In one embodiment of the present application, a secondary battery is provided.

[0089] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0090] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0091] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0092] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0093] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0094] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0095] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0096] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0097] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0098] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0099] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0100] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0101] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0102] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0103] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0104] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0105] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0106] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0107] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0108] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0109] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can choose according to specific actual needs.

[0110] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0111] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0112] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0113] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0114] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0115] In a fifth aspect, an embodiment of the present application proposes an electrical device, including the electrochemical device of the fourth aspect of the present application.

[0116] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0117] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0118] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0119] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0120] Example

[0121] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0122] The parameters of the positive electrode materials of Examples 1 to 24 of the present application and Comparative Examples 1 to 2 are according to the parameters in Table 1.

[0123]

[0124]

[0125] Embodiment 25

[0126] A method for preparing a positive electrode material comprises the following steps:

[0127] A coating layer is formed outside the core material lithium manganate, and the carboxyl group in the coating layer material reacts with the lithium manganate to obtain a positive electrode material.

[0128] Embodiment 26

[0129] A method for preparing a positive electrode material comprises the following steps:

[0130] The lithium manganate is reacted with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material.

[0131] Embodiment 27

[0132] A method for preparing a positive electrode material comprises the following steps:

[0133] The lithium manganate is mixed with a solution of ethylenediaminetetraacetic acid, so that the carboxyl group in the ethylenediaminetetraacetic acid reacts with the lithium manganate to form a coating layer on the surface of the lithium manganate, thereby obtaining a positive electrode material.

[0134] Embodiment 28

[0135] A method for preparing a positive electrode material comprises the following steps:

[0136] The lithium manganate and ethylenediaminetetraacetic acid solution were mixed and reacted at 30° C. for 1.5 h to form a coating layer to obtain a positive electrode material.

[0137] Performance Test:

[0138] The positive electrode materials of Examples 1 to 24 and Comparative Examples 1 to 2 were prepared into secondary batteries, wherein the preparation method is as follows:

[0139] Cathode slurry

[0140] The positive electrode materials of Examples 1 to 24 and Comparative Examples 1 to 2, binder PVDF, conductive agent carbon black, and CNT were dry-mixed in a ratio of 96:2:1.7:0.3 for 15 minutes, and then NMP was added and stirred at 1000 rpm for 120 minutes to finally obtain a uniform positive electrode slurry with a solid content of 70%.

[0141] Cathode sheet preparation

[0142] The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the coating mass is 0.015g / cm 2 The oven temperature is set to 130°C to dry the electrode sheet; then the positive electrode sheet is obtained through processes such as cold pressing, slitting, and welding the electrode ears.

[0143] Battery components and finished product preparation

[0144] The negative electrode material hard carbon, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96.8:0.4:1.7:1.1, and then coated on the negative electrode current collector copper foil. After drying, the negative electrode sheet is obtained by cold pressing, slitting and other processes.

[0145] Isolation film: Use PE isolation film.

[0146] The electrolyte selected is a 1.2 mol / L lithium hexafluorophosphate salt solution, and the organic solvent is an electrolyte prepared by ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a volume ratio of 5:2:3.

[0147] The positive electrode sheet, the separator, and the negative electrode sheet were assembled in a dry environment with a humidity of less than 2%, and after drying, the electrolyte was injected and packaged. A soft-pack battery with a capacity of 2.1Ah was prepared through a formation test, and an electrical performance test was performed.

[0148] Perform the following test:

[0149] At 45°C, the assembled battery was charged to 4.2V at 0.5C, left for 10 minutes, and then discharged to 2.5V at 1C. The above steps were repeated for the same battery, and the battery capacity after 800 cycles was recorded. The results are shown in Table 1.

[0150] As can be seen from Table 1, through Examples 1 to 24 and Comparative Examples 1 to 2, it can be seen that the compound containing a carboxyl functional group in the coating layer reacts with the inner core lithium manganese oxide to generate a compound containing an ester functional group to form an ion-conducting polymer, thereby in situ coating the compound containing a carboxyl functional group in the coating layer on the surface of the inner core lithium manganese oxide, thereby achieving in situ coating of the electrode active material, and improving the firmness of the bonding between the coating layer and the lithium manganese oxide through covalent bonds, thereby coating the lithium manganese oxide in the inner core, reducing the contact between the lithium manganese oxide and the electrolyte, and inhibiting the dissolution of manganese ions, thereby reducing the reaction of the electrode active material with the electrolyte, and improving the cycle performance of the battery.

[0151] As can be seen from Examples 1 to 12, different compounds containing carboxyl functional groups can react with the residual alkali on the surface of lithium manganate to generate compounds containing ester functional groups on the surface of lithium manganate to form ion-conducting polymers, thereby in-situ coating the carboxyl functional group-containing compounds of the coating layer on the surface of the inner core lithium manganate, thereby achieving in-situ coating of the electrode active material. When the number of carboxyl groups is 1 to 5, the consumption rate of the residual alkali can be increased, the residual alkali can be reduced, and the firmness of the connection between the coating layer and the inner core can be improved. The situation where the unreacted carboxyl groups increase the mass proportion of the coating layer can be reduced, reducing the impact on the mass proportion of the active material and improving the energy density of the battery.

[0152] It can be seen from Examples 1 to 9 that when the compound containing a carboxyl functional group also includes a nitrogen-containing group, the coordination effect between manganese and nitrogen can be used to further reduce the dissolution of manganese ions and improve the cycle performance of the battery.

[0153] It can be seen from Examples 10 to 12 that the nitrogen-containing group includes at least one of -NH2, -N- and -N=N-. Using at least one of the above nitrogen-containing groups is more conducive to the coordination and complexation of nitrogen atoms and manganese ions, improving the firmness of the combination of the coating layer and the core, and further improving the energy density and cycle performance.

[0154] It can be seen from Examples 13 to 18 that when the mass proportion of the coating layer in the positive electrode material is between 0.05% and 1%, the thickness of the coating layer can be made appropriate, which is beneficial to the rapid transmission of ions and electrons in the positive electrode material and reduces the impact on the energy density of the battery, while maintaining a good coating effect and reducing the contact between the active material and the electrolyte.

[0155] It can be seen from Examples 19 to 24 that the thickness of the coating layer is 1 to 20 nm, which can improve the coating performance of the core while reducing the direct contact between the core active material and the electrolyte, reducing the impact on the rapid transmission of lithium ions, and reducing the impact on the energy density of the battery.

[0156] In summary, in the positive electrode material proposed in the present application, the compound containing carboxyl functional groups in the coating layer reacts with the inner core lithium manganese oxide to generate a compound containing ester functional groups to form an ion-conducting polymer, thereby in situ coating the compound containing carboxyl functional groups in the coating layer on the surface of the inner core lithium manganese oxide, thereby achieving in situ coating of the electrode active material, and improving the firmness of the bonding between the coating layer and lithium manganese oxide through covalent bonds, thereby coating the lithium manganese oxide in the inner core, reducing the contact between the lithium manganese oxide and the electrolyte, and inhibiting the dissolution of manganese ions, thereby reducing the reaction of the electrode active material with the electrolyte, and improving the cycle performance of the battery.

[0157] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode material, characterized in that: It comprises an inner core and a coating layer at least partially coating the inner core, wherein the inner core comprises at least lithium manganate, the coating layer comprises a reaction product of a compound containing a carboxyl functional group and a residual alkali on the surface of the lithium manganate, and the reaction product contains an ester functional group.

2. The positive electrode material according to claim 1, characterized in that In the structural formula of a single compound containing a carboxyl functional group: The number of carboxyl groups is 1 to 5; optionally, the number of carboxyl groups is 1 to 4.

3. The positive electrode material according to claim 2, characterized in that The compound containing a carboxyl functional group includes at least one of 3-ethoxypropionic acid, fumaric acid, butanetetracarboxylic acid and biphenyl-3,3',5,5'-pentacarboxylic acid.

4. The positive electrode material according to claim 1 or 2, characterized in that The carboxyl functional group-containing compound further includes a nitrogen atom-containing group.

5. The positive electrode material according to claim 4, characterized in that In the structural formula of a single compound containing a carboxyl functional group, the number of the nitrogen atom-containing groups is 1 to 4; alternatively, the number of the nitrogen atom-containing groups is 1 to 2.

6. The positive electrode material according to claim 4 or 5, characterized in that The nitrogen atom-containing group includes at least one of -NH2, -N- and -N=N-.

7. The positive electrode material according to any one of claims 4 to 6, characterized in that The compound containing a carboxyl functional group includes at least one of ethylenediaminetetraacetic acid, nitrilotriacetic acid, 4-methyl-1-piperazineacetic acid and N,N-dihydroxyethylglycine.

8. The positive electrode material according to any one of claims 1 to 7, characterized in that The pH value of the core in a mixed solution with a core-to-water mass ratio of 1:10 is 7-11, and optionally, the pH value is 8-10.

9. The positive electrode material according to any one of claims 1 to 8, characterized in that The mass fraction of the material of the coating layer is w1, and the mass fraction of the material of the core is w2, wherein, 0.05%≤w1:(w1+w2)≤1%; optionally, 0.1%≤w1:(w1+w2)≤0.5%.

10. The positive electrode material according to any one of claims 1 to 9, characterized in that The coating layer has a thickness of 1 to 20 nm; optionally, the coating layer has a thickness of 1 to 10 nm.

11. The positive electrode material according to any one of claims 1 to 10, characterized in that The lithium manganate includes doped lithium manganate, and the molecular formula of the doped lithium manganate includes LiMn 2-α X α O4; Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium. The value of α is 0.001~0.

5.

12. The method for preparing a positive electrode material according to any one of claims 1 to 11, characterized in that: The following steps are involved: A coating layer is formed outside the core material lithium manganate, and the carboxyl group in the coating layer material reacts with the residual alkali on the surface of the core material lithium manganate to obtain a positive electrode material.

13. The method for preparing the positive electrode material according to claim 12, characterized in that: The step of forming a coating layer outside the core material lithium manganese oxide, and allowing the carboxyl group in the coating layer material to react with the core material lithium manganese oxide to obtain the positive electrode material comprises: The lithium manganate is reacted with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material.

14. The method for preparing the positive electrode material according to claim 13, characterized in that: The step of reacting lithium manganate with a compound containing both a carboxyl functional group and a nitrogen-containing group to form a coating layer on the surface of the lithium manganate to obtain a positive electrode material includes: The lithium manganate is mixed with a solution of ethylenediaminetetraacetic acid, so that the carboxyl group in the ethylenediaminetetraacetic acid reacts with the residual alkali on the surface of the lithium manganate to form a coating layer on the surface of the lithium manganate, thereby obtaining a positive electrode material.

15. The method for preparing the positive electrode material according to claim 14, characterized in that: The reaction time is 0.5 to 5 hours; optionally, the reaction time is 1 to 2 hours; and / or, The reaction temperature is 5 to 50°C; optionally, the reaction temperature is 20 to 40°C.

16. A positive electrode sheet, characterized in that: The invention comprises a positive electrode material as claimed in any one of claims 1 to 11 or a positive electrode material prepared by the method for preparing the positive electrode material as claimed in any one of claims 12 to 15.

17. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 16.

18. An electrical device, characterized in that: Comprising the battery of claim 17.